(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Herbal drug of Terminalia chebula the seed part have various therapeutic activity, hence the present study was undertaken to analysis of Terminalia chebula both in phytochemical and FTIR analysis belongs to functional group confirmation. The phytochemical analysis showed positive result for most of the tests assessed and FTIR showed positive result for alcohol, alkenes, aldehydes, aromatic compounds, nitro compound, ether, aliphatic compound, alkyl halides and isothiocyanate.